Climate change and agriculture: The role of international trade - Reilly, John M.; Hohmann, Neil (American Economic Review, 1993)
Predictions of future climate and atmospheric conditions are reviewed and the implications for agriculture in different areas of the world are identified. The SWOPSIM (static world policy simulation) model used to evaluate the worldwide economic effects of climate change is described. An economic sensitivity analysis of concurrent yield losses in major grain-producing regions considering the possibility of concurrent changes in production potential elsewhere in the world is reported. Agricultural impacts of climate change based on three general circulation models are evaluated.